English language proficiency level of Higher Secondary level students in Nepal - Sijali, Keshab Kumar (Journal of Advanced Academic Research, 2017)
The objective of this study is to investigate the proficiency level of English language of higher secondary level students in Nepal regarding their gender, nature of institution, medium of instruction and stream. The subject of this study comprises 529 learners from 22 higher secondary school of academic year 2015/6 among whom an English language proficiency test was conducted. The data obtained were analyzed using mean, Mann-Whitney U-test and Kruskal Wallis H-test of non-parametric test. The result showed that the English language proficiency level of higher secondary level students in Nepal was poor (M = 10.4490). Regarding the gender, the result showed that there was no statistically significant difference between female and male ELT students in their English language proficiency level. However, ELT students of government higher secondary level were found statistically significantly less proficient in English language than that of private higher secondary level .Similarly, the Nepali medium ELT students were found statistically significantly highly less proficient in English language than that of English medium. The result further showed that there was statistically significant difference in the English language proficiency level of higher secondary level students in Nepal from different streams